Grappling with Stigma and Celebrating Ingenuity with Failures and Negative Data - Heather Flannery (Moderator); Jose Arrieta; Debbie Bucci; Tom Savel (Blockchain in Healthcare Today, 2018)
(no abstract or summary available)